Assessing digital literacy levels and challenges among junior high school students in Yogyakarta - Listiana, Linda; Sari, Valentina Dyah Arum (Politeknik Negeri Jember, 2025)
Digital literacy is the ability to access, understand, analyse, evaluate, and create information in digital format through information and communication technology devices. Digital literacy skills among students are essential to enable them to engage effectively in the learning process to facilitate students in achieving learning goals. Students' skills in using digital media are related to their levels of digital literacy. The level of digital literacy has a correlation with students' readiness to utilize technology. This study aimed to determine the digital literacy level of junior high school students in Indonesia and the challenges faced by them. This study used a mixed-method approach. The research data was collected through questionnaires and interviews. Findings indicate that students’ digital literacy levels averaged 54.1%, classifying them as moderate. In addition, the challenges faced by students include limited knowledge about relevant websites, access constraints due to inadequate internet connections, and difficulties in understanding the features of word processing applications. Moreover, a collaborative approach from educators, stakeholders, and researchers is needed to address challenges and improve digital literacy to appropriate levels.